Wanprestasi atas Perjanjian Jasa Promosi oleh Influencer pada Media Sosial Ditinjau dari Perspektif KUH Perdata - Rifki Fadlurohman; Muhammad Faiz Mufidi (UNISBA Press, 2023)
Abstract. The purpose of this research is to examine the law concerning defaults on promotional service agreements by influencers and to determine how to resolve defaults that occur in the endorsement agreement. This study uses an approach known as